Effect of grape seed extract (Vitis labrusca L.) on soybean oil under thermal oxidation. Issue 5 (11th September 2017) - Freitas, Irene Rodrigues; Cattelan, Marília Gonçalves; Rodrigues, Mara Lina; Luzia, Débora Maria Moreno; Jorge, Neuza
Abstract : Purpose: This study aims to evaluate the effect of grape seed extract on the thermal oxidation of soybean oil. Design/methodology/approach: Four treatments were used: soybean oil (SO), butylhydroxytoluene (BHT), antioxidant at concentration of 100 mg/kg in soybean oil (BHTSO), grape seed extract at a concentration of 100 mg/kg in soybean oil (Extract), and mixture at a concentration of 50 mg/kg of grape seed extract (Mixture) and 50 mg/kg of BHT in soybean oil subjected to 180°C for 20 h. The total phenolic compounds were quantified by spectrophotometry using the Folin-Ciocalteu reagent. The antioxidant activity was evaluated by the ABTS +, DPPH and FRAP acid systems. The fatty acid composition and phytosterols were determined by gas chromatography (GC) and tocopherols were determined by high-performance liquid chromatography. Findings: Among the treatments studied, the Extract and the Mixture presented lower losses of total phenolic compounds, DPPH and FRAP, while BHTSO had an opposite effect. After 10 h of heating, the Mixture and the Extract were more effective in reducing the formation decomposition products, measured by the amount of total polar compounds. The Mixture resulted in higher retention of essential fatty acids at the end of heating. The Extract and Mixture showed higher retention rates of total tocopherols and the Mixture resulted in 338.71 mg/100 g ( P ≤ 0.05) of total phytosterol after 20 h of heating. Originality/value: Oils undergoing the heating process suffer major changes, requiring the addition of antioxidant compounds. As a result of the questioning on the use of chemical additives, research on natural antioxidants, as substitute to the synthetic ones, is increasing. Among the natural compounds with high antioxidant potential, the grape wastes such as its seeds are highlighted. Studies using grape seed extract are scarce.